Infestation of Palm Trees by Triatomines (Hemiptera: Reduviidae) in the State of Bahia, Brazil - Gurgel-Gonçalves, Rodrigo; Júnior, Gilmar Ribeiro; Costa Neto, Eraldo Medeiros da (EntomoBrasilis, 2012)
Palm trees play important roles as breeding and foraging habitats for sylvatic triatomines, vectors of Chagas disease. The occurrence of triatomines in peridomestic palm trees may increase the risk of invasion in households and should therefore be considered to develop prevention strategies. In order to investigate the infestation of palm trees by triatomines in the state of Bahia and to determine their natural infection with Trypanosoma spp., we sampled 183 palms in 12 municipalities between 2006 and 2011 using manual capture and/or mouse-baited adhesive traps. Triatomines were detected in 79 palms (43%) such as Copernicia prunifera, (Mart.) Becc., Mauritia flexuosa L. and Attalea spp. (Attalea burretiana Bondar or Attalea salvadorensis Glassman). In other palm species (Syagrus coronata (Mill) H.E. Moore, Attalea funifera Mart ex. Spreng, and Elaeis guineensis Jacq) triatomines were not detected. Rhodnius neglectus Lent, Triatoma sordida (Stål), and Triatoma pseudomaculata Corrêa & Espínola occurred in C. prunifera along the São Francisco River. In western Bahia, R. neglectus and Psammolestes tertius Lent & Jurberg were detected in M. flexuosa, while Triatoma tibiamaculata (Pinto) occurred in Attalea sp. in urban areas of Salvador on the coast of Bahia. Overall, 180 triatomines were captured, mainly R. neglectus. T. tibiamaculata had the highest rate of natural infection (61%). The results indicate that at least three species of palms are suitable habitats for triatomines in the state of Bahia and occur in peridomestic environment, what may enhance the probability of triatomine invasion into houses. Infestação de Palmeiras por Triatomíneos (Hemiptera: Reduviidae) no Estado da Bahia, Brasil Resumo. As palmeiras desempenham papéis importantes como habitats de reprodução e alimentação para triatomíneos silvestres, vetores da doença de Chagas. A ocorrência de triatomíneos em palmeiras peridomiciliares pode aumentar o risco de invasão desses insetos em domicílios e deve ser considerada para desenvolver estratégias de prevenção. Com objetivo de investigar a infestação de palmeiras por triatomíneos no Estado da Bahia e determinar a infecção natural desses insetos por Trypanosoma spp., foram amostradas 183 palmeiras em 12 municípios entre 2006 e 2011 utilizando captura manual e/ou armadilhas adesivas iscadas com camundongos. Os triatomíneos foram detectados em 79 palmeiras (43%) das espécies Copernicia prunifera (Mart.) Becc., Mauritia flexuosa L. e Attalea spp. (Attalea burretiana Bondar ou Attalea salvadorensis Glassman). Em outras espécies de palmeiras (Syagrus coronata (Mill) H.E. Moore, Attalea funifera Mart ex. Spreng e Elaeis guineensis Jacq) não foram detectados triatomíneos. Rhodnius neglectus Lent, Triatoma sordida (Stål), e Triatoma pseudomaculata Corrêa & Espínola ocorreram em C. prunifera ao longo do rio São Francisco. No extremo oeste da Bahia, R. neglectus e Psammolestes tertius Lent & Jurberg foram detectados em M. flexuosa, enquanto Triatoma tibiamaculata (Pinto) ocorreu em Attalea sp. em áreas urbanas de Salvador. No total, 180 triatomíneos foram capturados, principalmente R. neglectus. A maior taxa de infecção natural (61%) foi observada em T. tibiamaculata. Os resultados indicam que pelo menos três espécies de palmeiras são habitats favoráveis para triatomíneos no estado da Bahia e ocorrem no ambiente peridomiciliar, o que pode aumentar a probabilidade de invasão de triatomíneos nas casas.